KEMAJUAN SISTEM TEKNOLOGI BERIKAN PENGARUH BESAR TERHADAP PERKEMBANGAN E-COMMERCE DI INDONESIA - adelia armaya (JEBS (Journal of Economic and Business Student), 2023)
Technological advances have had a major impact on the progress of e-commerce in Indonesia. E-commerce is electronic commerce which is a collection of technologies, applications and businesses that connect companies or individuals as consumers to exchange goods and services electronically, electronic transactions and exchange information via the internet or television. Many millennials have switched to e-commerce as time has progressed. The purpose of this study is to identify how technological advances affect the development of e-commerce in Indonesia. This study uses a qualitative method, namely understanding social phenomena through a holistic picture and increasing understanding in depth. The results of this study indicate that technological advances have indeed had a major impact on the development of e-commerce in Indonesia due to changes in people's behavior in terms of shopping.